แนวทางการเพิ่มการใช้รถรับส่งนักเรียนในกรุงเทพมหานคร - อัจฉรา ลิ้มมณฑล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
School bus is one of ridesharing modes for commuting to schools by children. School bus, if successfully implemented, would reduce peak-hour automobile travels and increase student’s travel safety. The objective of this study is to unveil the factors influencing parental decisions regarding their child’s use of school bus in Bangkok. Five schools with school buses in Chatuchak District, inner Bangkok, were studied. This includes interviews of key managing teachers and questionaire distribution to students’ parents. 419 of 619 questionaires were returned and analyzed using descriptive statistics as well as logit choice model equations. The results reveal parents’ characteristics which are likely to use school bus than others such as have business owners or business employees occupations, have high income and have more than one child in a particular school. Main reasons of why parents are not using the service are due to short school trip distance and Thai culture of parental care. The study data suggest that to government and private sectors would develop strategies to both schools and parents to promote the use of school bus by showing the benefits and importance of school bus service and government agencies should allocate more funds in order to persuade parents to use more school bus services.